sharon asked in Science & MathematicsMathematics · 2 months ago

# how to solve (8-5 ÷ 6) 6 = 43?

Relevance
• 2 months ago

(8 - 5 ÷ 6) 6

as written, we divide first:

(8 - 5/6) 6

Now we subtract, so we'll need a common denominator:

(48/6 - 5/6) 6

(43/6) 6

Now multiply.  the 6's cancel out:

43

• 2 months ago

Apply PEMDAS

(8-5/6)6

((8*6-5)/6)6

((48-5)/6)6

(43/6)6

=43

• 2 months ago

What operand symbol is in the place of my underline ... ")_6" AND THE ANSWER IS * (as in the times sign) ... and then the equation works.

• sepia
Lv 7
2 months ago

(8 - 5 ÷ 6) 6

= 43

• 2 months ago

nothing to solve

(8-5 ÷ 6) 6

division has precedence

(8 – 5/6)5

(48/6 – 5/6)6

(43/6)6

43

so the equality is correct.

• 2 months ago

By distributive law:

(a - b) × c = a × c - b × c

Now,  a = 8,  b = 5 ÷ 6  and  c = 6

Hence, (8 - 5 ÷ 6) × 6

= 8 × 6 - 5 ÷ 6 × 6

= 48 - 5

= 43

• 2 months ago

(8 - 5 ÷ 6) 6

= 43

• 2 months ago

you need to restate your question...looks like you have a typo